Natural Treatment Alternative for Psoriasis: A Review on Herbal Resources - Kamlesh Kumar Singh, Surendra Tripathy (Journal of Applied Pharmaceutical Science, 2014)
Psoriasis is an immune mediated inflammatory disease, which is having no permanent cure. Though, there are several treatment methods to treat psoriasis, no particular medication claims a satisfactory and complete remedy. A wide range of synthetic therapeutic agents have also been reported to cause psoriasis as their adverse effect. Herbal drugs by virtue of their safe nature and easy availability may lend themselves as potential anti-psoriatic moieties. Before developing a herbal drug candidate the key players of psoriasis to develop should be thoroughly understood, which includes T-cell activation, T-cell trafficking, Cytokinase inhibition. The paper aims to explore the proliferation and activation mechanism of psoriasis, psoriasis caused by certain drugs and different plant resources known to have anti-psoriatic potential. A more scientific investigation on these herbal resources must be performed to develop a potent, safe and reliable therapy.
Keywords: Psoriasis, Inflammation, Herbal drugs, T-Cell Activation, proliferation.